Role of ICT in Sustainable Growth of Entrepreneurship in Bangalore Rural District - Bavle, Sushama; Shekar, Ms. Manjula (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurial growth has become synonymous with economic growth of a nation. To achieve sustained development, every nation has to focus on sustained entrepreneurship development. This can be achieved through urban and rural entrepreneurial development. But, Rural India remains far behind Urban India indicating the urgent need to initiate steps to reduce the gap. Globally, e-business has become parallel to traditional business and has become an important feature of sustained growth in entrepreneurial ventures. It is in this background, a research study titled ‘Role of ICT in sustainable growth of Entrepreneurship in Bangalore Rural District’ was carried out. Data was collected from five taluks of Bangalore Rural District (Sample of 302 rural entrepreneurs) using random sampling method. The findings of the study revealed that, among all the demographic variables, education emerged significant in the use of ICT in business and impact of use of ICT in business. Gender was another demographic profile which was significant in use of ICT devices and facing the challenges in the use of ICT. The use of ICT was found to be very low in various aspects of business. But, where ICT was used, the impact on business was positive. The findings indicate the crucial need to focus on education, infrastructure development and understand the importance of removing the rural-urban divide and the digital divide.